Evaluation of DHF Surveillance Based on Attributes in Pasuruan District - Ahmad Zamzam Hariro; Chatarina Umbul Wahyuni; Supa’at Setia Hadi (Health Notions, 2019)
Dengue Hemorrhagic Fever (DHF) is one of health problems in Pasuruan that the number of sufferers was increase. Those problems would not actually happen if the surveillance gose well. The purpose of this study was to describe the problem of DHF surveillance based on attributes as well as provide an alternative solution. This research was a descriptive study with evaluation study design. This study was conducted in 16 Public Health Centers and health office of Pasuruan District. Data were collected through interviews with DHF officers in 16 PHC and health office of Pasuruan District, using questionnaires, and document analysis against DHF data reports. The problems was not simple in feedback, not acceptable in feedback, and not on time in feedback because the feedback only give every 3 months. Data was not representative because data can’t describe population based on time and place. Data was unstable because there were 41.25% respondent that loss of data. Provide personal computers for program officers is needed to keep the data from lost and always available. Motivate the public health centers to form an independent jumantik cadre with funding sources from public health center or sub district for optimal PSN and data reports. Keywords: DHF, Surveillance, Attributes